Analysis of instructional design model with involvement of instructors for blended learning / Fatin Farzana Azizan - Azizan, Fatin Farzana (2016)
Blended learning has become an important alternative learning platform to deliver knowledge in higher education. It allows instructors or students to access education at any time or place. Blended learning platforms also consist of virtual worlds such as Secondlife (SL), which allows users to interact synchronously in a virtual environment. Enriched blended learning can be developed by implementing an instructional design model that can create better learning outcome. However, the model is absent with the element of instructor’s involvement that can be portrayed through verbal and non-verbal immediacy behaviours. This is critical in obtaining better learning outcome. Hence, this research aims to adapt an instructional design model that includes element of instructor’s involvement in blended learning. To achieve the research’s aim, an experiment was conducted to determine the level of immediacy instructor avatar perceived by students. An interview and questionnaire were conducted once the experiment ended to obtain the results from the experiment. SSM phases 1 to 5 were executed to obtain an idea on how the instructor’s involvement in terms of immediacy behaviours can be included in the instructional design model. The experiment results demonstrated that students perceived a high level of verbal immediacy behaviours and a low level of non-verbal immediacy behaviours portrayed by instructor avatar. Students, however, stated their preferences to have instructor avatar portray non-verbal immediacy behaviours as it can provide better interaction, and prefer to have instructor in the learning session. From executing SSM phases, immediacy behaviours were determined on how it can be included. This led to the chosen model to be modified and included with instructor’s involvement. For future research, it is recommended to explore the placement of more than one instructor in a blended learning session. It is also suggested for the developed model to be applied in the real world eventually.